Direct medical cost of COVID-19 in children hospitalized at a tertiary referral healthcare center in Mexico City - Reyes-López, Alfonso; Jimenez-Juárez, Rodolfo Norberto; Salinas-Escudero, Guillermo; Avilés-Robles, Martha Josefina; Martínez-Valverde, Silvia; Granados-García, Víctor; Garduño-Espinosa, Juan (Frontiers in Public Health, 2023)
Introduction Despite the end of the COVID-19 pandemic being declared by the WHO, the economic consequences are far from over. One of these implications was the cost of inpatient care for health institutions. To date, some studies have examined the economic burden of COVID-19 in the adult population but only a few have focused on child populations. Objective To estimate the direct medical costs of COVID-19, focusing on children in Mexico. Method Data about resources consumed during hospital stays were extracted from the medical records of patients hospitalized at a Mexican tertiary healthcare institution. Other sources of information were the unit prices of inputs and the salaries of health personnel. A micro-costing methodology was used to obtain cost results by age group over different hospital areas. Data analysis was performed with descriptive statistics and regression models to evaluate the predictors of total cost. Results One hundred and ten medical records were reviewed of which 57.3% corresponded to male patients and the mean age was 7.2 years old. The estimated average cost per patient was US$5,943 (95% CI: US$4,249–7,637). When the costs of the three clinical areas were summed, only the 5–10 years old group showed a maximum cost of US$14,000. The regression analysis revealed the following factors as significant: sex, age, staying at an emergency room, having a positive bacterial culture, and having comorbidities. Discussion The cost results were somewhat similar to those reported in children from the USA, but only regarding low severity COVID-19 cases. However, comparability between these types of studies should be done with caution due to the huge differences between the healthcare systems of countries. The study cost results may help public decision-makers in budget planning and as inputs for future cost-effectiveness studies about interventions regarding COVID-19.